1998
DOI: 10.1074/jbc.273.12.6769
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Residues Phosphorylated in Vitro by Different C-terminal Domain Kinases

Abstract: The C-terminal part of the largest subunit of eukaryotic RNA polymerase II is composed solely of the highly repeated consensus sequence Tyr 1 -Ser 2 -Pro 3 -Thr 4 -Ser 5 -Pro 6 -Ser 7 . This domain, called the C-terminal domain (CTD), is phosphorylated mostly at serine residues during transcription initiation, but the precise role of this phosphorylation remains controversial. Several protein kinases are able to phosphorylate this sequence in vitro. The aim of this work was to define the positions of the amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 67 publications
11
102
1
Order By: Relevance
“…Reduced CTD phosphorylation has also been observed in embryos depleted for ttb-1, the C. elegans TFIIB homolog, and is consistent with a general defect in RNAPII transcription (24). In vitro, CDK7 possesses robust CTD-kinase activity specific for phosphorylation at Ser-5 of the CTD consensus repeat (42)(43)(44)(45). Interestingly, using the monoclonal antibodies H5 and H14 (30,31), we found that phosphorylation at both Ser-2 and Ser-5 is reduced in cdk-7 mutants.…”
Section: Discussionmentioning
confidence: 84%
“…Reduced CTD phosphorylation has also been observed in embryos depleted for ttb-1, the C. elegans TFIIB homolog, and is consistent with a general defect in RNAPII transcription (24). In vitro, CDK7 possesses robust CTD-kinase activity specific for phosphorylation at Ser-5 of the CTD consensus repeat (42)(43)(44)(45). Interestingly, using the monoclonal antibodies H5 and H14 (30,31), we found that phosphorylation at both Ser-2 and Ser-5 is reduced in cdk-7 mutants.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, CTD phosphorylation sites have been reported from studies using a GST-CTD fusion protein, CTD heptapeptide repeat peptides, and a free form of intact Pol II; for example, TFIIH phosphorylates Ser-5, and Cdk8-cyclin C of the SRB-and Med-containing complex NAT phosphorylates Ser-2 and Ser-5 (58,64). Since TFIIH is the only CTD kinase to exist in the reconstituted active PIC at transcription, we thought that phosphorylation of the CTD heptapeptide repeats (YSPTSPS; the first Tyr [Y] is here designated Tyr-1) of Pol II in the active PIC must correspond to the conformational change of Pol II to be processive.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, serum-stimulated CTD kinase activity is resistant to inhibiton by the drug 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) (Dubois et al, 1994;Bonnet et al, 1999), which inhibits CDK7, CDK8, and CDK9 but not ERK-1/2 CTD kinase (Marshall and Price, 1995;Yankulov et al, 1995;Rickert et al, 1999). Finally, recombinant ERK-1/2 has been shown to ef®ciently phosphorylate the RNAP II CTD in vitro (Trigon et al, 1998;Bonnet et al, 1999). Interestingly, ERK-1/2-mediated CTD phosphorylation results in the generation of a novel RNAP IIm form that can be discriminated from the RNAP IIA and IIO forms by SDS±PAGE analysis .…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
“…The physiological role of RNAP IIm remains to be investigated. However, RNAP IIm appears not to be engaged in transcription and is exclusively phosphorylated at position Ser-5 (Trigon et al, 1998;Bonnet et al, 1999), whereas the pool of (transcriptionally active) RNAP IIO in unstimulated mammalian cells is phosphorylated on both Ser-5 and Ser-2 (Bregman et al, 1995;Patturajan et al, 1998;Castan Ä o et al, 2000). Finally, it is pertinent to note that CTD phophorylation by ERK-1/2 kinases has also been implicated in the repression of RNAP II in mature Xenopus oocytes as well as in rabbit and mouse zygotes prior to zygotic gene activation (Bellier et al, 1997a,b).…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
See 1 more Smart Citation